Analisis Kesalahan Siswa dalam Menyelesaikan Soal Matriks Ditinjau dari Pendekatan Realistic Mathematics Education (RME) - Weti Anggriani; Marniati, Marniati; Tahir, Tahir (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to analyze students' errors in solving matrix problems from the Realistic Mathematics Education (RME) approach. The method used is a qualitative descriptive study with 33 students of grade XI of SMA Negeri 1 Pomalaa as research subjects. Data were collected through tests, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that students still experienced errors in understanding the problem (9.09%), conceptual errors (27.27%), procedural errors (42.42%), and arithmetic operation errors (45.45%). The most dominant errors were arithmetic operation errors, especially in matrix multiplication, determinants, and matrix inverses. In addition, students' conceptual understanding ability was in the high category at 27.27%, the medium category at 66.67%, and the low category at 6.06%. Factors causing errors included a low understanding of basic matrix concepts, lack of accuracy in calculations, and difficulty understanding contextual problems. The conclusion of this study shows that although the RME approach helps students connect matrix concepts with real situations so that learning becomes more meaningful, students still need to strengthen their conceptual understanding, calculation accuracy, and the ability to systematically organize solution steps to minimize errors in solving matrix problems.   Keywords: Error Analysis, Matrix, RME Approach, Conceptual Understanding, Mathematics Learning